2006
DOI: 10.1037/0022-3514.90.4.629
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the psychological underpinnings of the moral mandate effect: Motivated reasoning, group differentiation, or anger?

Abstract: When people have strong moral convictions about outcomes, their judgments of both outcome and procedural fairness become driven more by whether outcomes support or oppose their moral mandates than by whether procedures are proper or improper (the moral mandate effect). Two studies tested 3 explanations for the moral mandate effect. In particular, people with moral mandates may (a) have a greater motivation to seek out procedural flaws when outcomes fail to support their moral point of view (the motivated reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
181
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(194 citation statements)
references
References 55 publications
10
181
1
2
Order By: Relevance
“…For example, in their research on 'moral spillover', Mullen and Nadler (2008) found that when participants were asked to summarize a court case involving a doctor who performed an illegal late-term abortion, pro-choice participants were more likely to steal pens provided by the experimenter if the story indicated that the doctor had been found guilty than if he had been found innocent. The researchers hypothesized that because participants read about the legitimation of a moral position with which they disagreed, they reacted, or 'acted out', by engaging in immoral behavior (also see Mullen & Skitka, 2006). In Experiment 1, participants in the relativist condition may have cheated more because the relativist argument defended and legitimated a moral position that they found morally reprehensible, to which they reacted by engaging in immoral behavior themselves.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in their research on 'moral spillover', Mullen and Nadler (2008) found that when participants were asked to summarize a court case involving a doctor who performed an illegal late-term abortion, pro-choice participants were more likely to steal pens provided by the experimenter if the story indicated that the doctor had been found guilty than if he had been found innocent. The researchers hypothesized that because participants read about the legitimation of a moral position with which they disagreed, they reacted, or 'acted out', by engaging in immoral behavior (also see Mullen & Skitka, 2006). In Experiment 1, participants in the relativist condition may have cheated more because the relativist argument defended and legitimated a moral position that they found morally reprehensible, to which they reacted by engaging in immoral behavior themselves.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying a situation in which D dwarfs B, Skitka and colleagues argue that procedural fairness assessments are of little importance for individuals who have a strong moral conviction on the outcome. 17 Mullen and Skitka 2006;Skitka 2002. Another alternative discussed in the literature is that outcome favorability interacts with subjective procedural fairness assessments to mitigate negative reactions to an unfavorable outcome (e.g., Bianchi et al 2015).…”
Section: How Outcome Favorability Intervenes In the Processmentioning
confidence: 99%
“…Of these 28, 22 expressed the view that the organization managed this process well, two felt that the organization had generally not managed it well, and four provided mixed responses suggesting that on some occasions it was managed well and on others badly. What this meant was the organizational narrative had constructed the meaning of the changes such that job loss and financial misfortune themselves were not seen as a matter that concerned ethics -the only 'moral mandate' (Mullen and Skitka, 2006) that the employees held their organization to was the requirement for people to be treated fairly on departure. In this case, the perception of a high level of procedural justice reduced the sense of adversity among both those retrenched and those who remained (Brockner et al, 1994) while apparently being used instrumentally (rather than ethically) to control employee behaviour (Fortin and Fellenz, 2008).…”
Section: The Refiguration Of V-tech and The Limiting Of Ethical Concernsmentioning
confidence: 99%